2015
DOI: 10.1063/1.4931427
|View full text |Cite
|
Sign up to set email alerts
|

Neutron, fluorescence, and optical imaging: An in situ combination of complementary techniques

Abstract: An apparatus which enables the simultaneous combination of three complementary imaging techniques, optical imaging, fluorescence imaging, and neutron radiography, is presented. While each individual technique can provide information on certain aspects of the sample and their time evolution, a combination of the three techniques in one setup provides a more complete and consistent data set. The setup can be used in transmission and reflection modes and thus with optically transparent as well as opaque samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…A detailed description of the home-built imagingapparatus to perform optical transmission imaging (OI) and fluorescence imaging (FI) experiments concurrently with neutron radiography (NR) can be found elsewhere. 31 The sample was irradiated with a parallel beam of light and a collimated neutron beam at the cold neutron imaging facility ICON at the Paul Scherrer Institute (Villigen, Switzerland) and time series of images were recorded with separate CCD cameras for each imaging technique. The chosen distance of the neutron source aperture, L, and diameter of the aperture, D ap , yielded L/D ap = 343.…”
Section: B Combined Imaging Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed description of the home-built imagingapparatus to perform optical transmission imaging (OI) and fluorescence imaging (FI) experiments concurrently with neutron radiography (NR) can be found elsewhere. 31 The sample was irradiated with a parallel beam of light and a collimated neutron beam at the cold neutron imaging facility ICON at the Paul Scherrer Institute (Villigen, Switzerland) and time series of images were recorded with separate CCD cameras for each imaging technique. The chosen distance of the neutron source aperture, L, and diameter of the aperture, D ap , yielded L/D ap = 343.…”
Section: B Combined Imaging Experimentsmentioning
confidence: 99%
“…In a typical experiment, the sample was constrained between two glass plates in a specifically designed sample cell that consisted of an aluminum body and quartz glass windows. 31 The cell was aligned with respect to the neutron and light beams. As neutron radiography experiments can only be performed at large scale facilities where beam time is severely limited, time series of images were recorded for a maximum of 3-8 h. It was found that for the FI experiments, and especially when the larger dextran molecules were used as diffusants, much longer measurement times would be favorable.…”
Section: B Combined Imaging Experimentsmentioning
confidence: 99%
See 3 more Smart Citations